ANALYSIS OF MUSTAHIQ CRITERIA FOR PRODUCTIVE ZAKAT IN BAITUL MAL WEST ACEH IN MAQASHID SHARIA PERSPECTIVE - Irta Nadillah; Iqbal, muhammad (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
Zakat is one of the obligations in Islam that plays an important role in creating social welfare and reducing economic inequality. In its development, zakat is not only given in consumptive form, but also productively, which aims to empower mustahiq economically. This study aims to analyse the criteria of productive mustahiq zakat in Baitul Mal Aceh Barat and evaluate the relevance of these criteria with maqashid sharia principles. The methods used are in-depth interviews with zakat managers and productive zakat experts, as well as documentation studies and direct observation in the field. The results showed that the criteria of productive zakat mustahiq applied in Baitul Mal Aceh Barat are only given to the poor and needy who face economic difficulties, by considering the business potential of prospective zakat recipients so that they can manage the assistance effectively to achieve economic independence. The application of these criteria is very relevant to the principles of maqashid sharia, such as hifz al-mal, hifz al-'ird, and hifz al-nafs, because it not only fulfils the basic needs of mustahiq, but also empowers them to be economically independent, improve dignity, and maintain the welfare of the soul, in line with the long-term goal of improving the quality of life and social welfare.